Study on Mixed Convection Heat Transfer in Vertical Ducts with Radiation Effects - Rajamohan, Ganesan; Narayanaswamy, Ramesh; Perumal, Kumar (World Academy of Science, Engineering and Technology, 2011)
Experiments have been performed to investigate the radiation effects on mixed convection heat transfer for thermally developing airflow in vertical ducts with two differentially heated isothermal walls and two adiabatic walls. The investigation covers the Reynolds number of Re = 800 to Re = 2900, heat flux varied from 256 W/m2 to 863 W/m2, hot wall temperature ranges from 27°C to 100 °C, aspect ratios 1 & 0.5 and the emissivity of internal walls are 0.05 and 0.85. In the present study, combined flow visualization was conducted to observe the flow patterns. The effect of surface temperature along the walls was studied to investigate the local Nusselt number variation within the duct. The result shows that flow condition and radiation significantly affect the total Nusselt number and tends to reduce the buoyancy condition.